Uplink bit combining for multiple base‐stations MIMO with applications to CoMP systems. Issue 2 (19th August 2014) - Leib, Harry; Lin, Wenjing
Abstract: This work considers a simple bit level combining technique, aided by robust bit reliability information, for uplink collaborating multiple‐input multiple‐output (MIMO) base‐stations (also known as macrodiversity MIMO), operating over composite Rayleigh‐lognormal fading channels. Bit reliability weights based on a robust modification of the logarithmic likelihood ratio, combined with instantaneous symbol signal‐to‐noise ratio information, are derived for different local MIMO detection schemes. This bit reliability information is used at the fusion center, together with locally detected data, for combining and producing final information bits delivered to the destination. Computer simulation results confirm that such bit level combining techniques, when used with minimum mean squared error ordered successive interference cancelation and also with sphere decoding maximum likelihood local detectors, provide significant performance improvements over non‐collaborative base‐stations systems. Performance gains are maintained even when these schemes suffer from channel estimation errors and also in the presence of space correlation. Low backhaul overhead and performance advantages make these bit level combining techniques attractive for applications in next generation cellular systems employing coordinated multi‐point (CoMP) technology, as well as for other collaborative MIMO communication schemes.Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This work considers a simple bit level combining technique, aided by bit reliability information, for uplink collaborating multiple‐input multiple‐output base‐stations. Bit reliability weights based on a robust modification of the logarithmic likelihood ratio, combined with instantaneous symbol signal‐to‐noise ratio information, are derived for various local multiple‐input multiple‐output detection schemes. Computer simulation results confirm that such bit level combining techniques provide significant performance improvements over non‐collaborative base‐stations systems. Such techniques could be attractive for uplink cellular systems employing CoMP technology.